Muslims' right to freedom of religion in Malaysia: piercing through the confusion and contradictions - Ab Aziz, Shamrahayu (LexisNexis, 2007)
There has been a string of courts decision on the right to religious freedom in Malaysia. Despite that, the interpretations to the relevant constitutional provision are still shrouded in mystery and contradictions. This is particularly when the decisions concern Muslims right to freedom of religion. This paper seeks to highlight some of the reported decisions on the issue. In ore rot understand the Muslims right to religious freedom; reference is also made to the juristic opinions on the Muslims right to freedom of religion. Although the case study concentrates on the Muslims rights to religious freedom, it is significant for it represents the courts attitude towards the right to religious freedom in Malaysia.